Application of Roboduino ATMega 2560 in the Making of the Fire Extinguisher Beetle Robot - Saut Situmorang (Journal of Science Technology (JoSTec), 2020)
Rapid technological advances, especially in technology such as robots, provide a lot of help for humans in tasks that are difficult for humans to do. As in the case of fire disasters that often occur, it has caused many casualties and property losses. When the fire is extinguished, there is a risk that must be borne by the firefighting team when extinguishing the fire inside something. Risks that can occur, such as being hit by objects falling from the roof of a building or fires that are getting worse grow up. In this study, a prototype fire fighting beetle robot will be made where the simulation is carried out by making a fire in an area. Implementation is done by controlling the robot with applications that include the ability to move, detect hotspots and extinguish fires. Prototype of Fire Detection using Infrared Flame Sensor Based on Arduino Atmega 2560 consists of 3 main blocks, namely: Infrared Flame Sensor, Notification, and Fire Extinguisher. This prototype was made so that later it can be realized so that it can help the firefighters in the event of a fire, especially in areas that are difficult to reach by fire engines.